2015
DOI: 10.3389/fmicb.2015.00120
|View full text |Cite
|
Sign up to set email alerts
|

xCT, not just an amino-acid transporter: a multi-functional regulator of microbial infection and associated diseases

Abstract: Expression of xCT, a component of the xc– amino-acid transporter, is essential for the uptake of cystine required for intracellular glutathione (GSH) synthesis and maintenance of the intracellular redox balance. Therefore, xCT plays an important role not only in the survival of somatic and immune cells, but also in other aspects of tumorigenesis, including the growth and malignant progression of cancer cells, resistance to anticancer drugs, and protection of normal cells against oxidative damage induced by car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…This may be beneficial if the goal is to trigger an immune response. Interestingly, the system transporter SLC7A11 is required for entry of Kaposi’s sarcoma-associated herpesvirus into certain cells [ 82 ], a process likely to disrupt normal glutathione homeostasis. Likewise infection of immune cells with the human immunodeficiency virus type-1 (HIV-1) is well know to cause dysregulation of glutathione homeostasis [ 83 , 84 ], possibly enhancing sensitivity to ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This may be beneficial if the goal is to trigger an immune response. Interestingly, the system transporter SLC7A11 is required for entry of Kaposi’s sarcoma-associated herpesvirus into certain cells [ 82 ], a process likely to disrupt normal glutathione homeostasis. Likewise infection of immune cells with the human immunodeficiency virus type-1 (HIV-1) is well know to cause dysregulation of glutathione homeostasis [ 83 , 84 ], possibly enhancing sensitivity to ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…As induction of xCT has been reported in response to a number of different stimuli (for review see Bridges R J et al, ; Lewerenz et al, ; Dai, Noverr, Parsons, Kaleeba, & Qin, ; Massie et al, ), the possibility exists that other cell types than astrocytes, microglia in particular, may under certain conditions start expressing xCT. Most evidence for microglial xCT expression comes from in vitro studies, but there are some reports on induced xCT expression in reactive microglia in vivo (for references see: Bentea et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several lines of evidence revealed that the temporal interaction between integrins α3β1 and xCT/CD98 is relevant to cell adhesion, fusion, proliferation and the integrin-dependent signal transduction [ 26 , 35 ]. Noteworthily, the xCT/CD98 complex, a cystine/glutamate exchange transporter, naturally functions to maintain the intracellular redox balance and protects cells from death induced by oxidative stress [ 35 , 36 ]. Based on the mentioned roles of integrins α3β1 and xCT/CD98 in cells, we therefore propose that elevated levels of integrin α3β1 and xCT/CD98 in endothelial and epithelial cells caused by high glucose may facilitate subsequent KSHV infection.…”
Section: Discussionmentioning
confidence: 99%